Literary Alchemist : The Writing Life of Evan S. Connell - Paul, Steve, 1953- (Book collections on Project MUSE., 2021)
"Evan S. Connell (1924-2013) emerged from the American Midwest determined to become a writer. He eventually made his mark with attention-getting fiction and deep explorations into history. This first portrait and appraisal of an under-recognized American writer is based on personal accounts by friends, relatives, writers, and others who knew him; extensive correspondence in library archives; and insightful literary and cultural analysis of Connell's work and its context"--